Clinical evaluation of non-syndromic scaphocephaly surgically corrected with the procedure of total vertex craniectomy. Issue 9 (September 2018) - Kreppel, Matthias; Kauke, Martin; Safi, Ali-Farid; Grandoch, Andrea; Pocek-Behn, Nina; Nickenig, Hans-Joachim; Zöller, Joachim
Abstract: The present investigation constitutes a retrospective evaluation of the outcome in children who received surgical correction of a scaphocephalic phenotype by median total vertex craniectomy. Between September 2009 and September 2015, a total of 35 infants with non-syndromic scaphocephaly were treated according to the same standardized operative technique of total vertex craniectomy by a single surgeon approach. At the time of surgery, the patients were between 3 and 12 months of age, with a median of 5 months. The mean duration of the procedure was 94 min. The duration of postoperative follow-up was a mean of 24 months (range 6–49 months). A total of 34 (97%) patients were successfully treated by total vertex craniectomy and were thus classified as category I according to the Whitaker score. Only one individual was assigned to category IV, necessitating secondary major craniofacial corrective surgery. Aesthetic outcomes were excellent in 34 cases and poor in one case. No major complication occurred. The reoperation rate was 3%. The surgical method we present herein is a wide median craniectomy which can be applied in young individuals with non-syndromic single-suture scaphocephaly.